Greenness assessment of a molecularly imprinted polymeric sensor based on a bio-inspired polymer - Hamees A. Adawy; Maha A. Hegazy; Samah S. Saad; Amr M. Bekhet; Shereen A. Boltia (BMC Chemistry)
Abstract Methyldopa, a synthesized dopamine substitute with phenolic, amine, and carboxylic groups, was used to create a selective molecular imprinted polymer (MIP) for detecting formoterol fumarate dihydrate (FFD), a long-acting beta2-agonist for asthma and COPD. The bio-inspired polymer (MD) was electro-grafted onto a pencil graphite electrode (PGE) using cyclic voltammetry in a phosphate buffer (pH 6.5). An indirect method involving a redox probe (ferrocyanide/ferricyanide) and differential pulse voltammetry measured FFD binding to the MIP’s 3D cavities. The sensor showed a linear response range from 1 × 10⁻⁹ M to 2 × 10⁻¹⁰ M, with a detection limit of 1.7 × 10⁻¹¹ M. The polymethyldopa (PMD) and FFD interaction was assessed by UV spectroscopy, and the method was validated per ICH guidelines. Green analytical approaches, including RGB and GAPI, were also implemented. The goal was to use advances in molecularly imprinted polymers to develop a more precise and selective electrochemical sensor for FFD quantification.